Evaluation of the Mandibular Function, after Nonsurgical Treatment of Unilateral Subcondylar Fracture: A 1-Year Follow-Up Study. Issue 3 (September 2016) - Sudheesh, K.M.; Desai, Rajendra; Siva Bharani, K. Sn; Subhalakshmi, S.
There are no clearly defined guidelines for when an open or closed treatment is indicated for treatment of mandibular condylar fractures. The aim of the study is to analyze the mandibular function after nonsurgical treatment of unilateral subcondylar fractures, in a prospective study. A prospective study was conducted on 30 patients with unilateral mandibular subcondylar fracture undergoing nonsurgical treatment. Clinical and radiographic examinations were done prior to treatment and at 12-month follow-up. Pain, perceived occlusion, mouth opening, protrusion, and horizontal movements of the mandible were evaluated by clinical examination. Radiologic evaluation was done using Panoramic and Reverse Towne's radiographs. At 12-month follow-up, there was minimal pain in the temporomandibular joint region, there was an improvement in the perceived occlusion, and mouth opening did not reduce. There was insignificant absolute difference between left and right lateral mandibular movements. The amount of increase in the protrusion of mandible was insignificant. On radiographic evaluation, the degree of coronal and sagittal displacement was insignificant at follow-up. Mean ramus height pretreatment and 12 months posttreatment were 0.98 ± 0.50 and 0.87 ± 0.47, respectively. Based on this study, patients had adequate mandibular function and minimal pain after nonsurgical treatment. Unilateral subcondylar fractures of the mandible can be treated nonsurgically in patients with minimal occlusal discrepancies, adequate mouth opening, minimal displacement of condyle, and minimal ramus height shortening.